Evaluation of the profile of student attitudes about death in the pandemic of COVID-19 (Research, Society and Development, 2023)
Nurses are directly exposed to death processes, as well as being able to deal with the suffering of a patient in the process of death and his family is a necessary competence, whose approach requires discussion in several contexts. Identify the profile of students' attitudes about death during the COVID-19 pandemic. Descriptive, exploratory, cross-sectional and quantitative study, approved by the Research Ethics Committee under opinion: 5,149,850. A sociodemographic questionnaire and the Profile Assessment Scale of Attitudes About Death were used, which were collected from February to April 2022. The data were stored in the Excel program, submitted to descriptive analysis, expressed through means, standard deviation and medians. For the relationship between the attitudes and characteristics of the participants, the significance test was applied. Sample in 120 participating students, most between 21 and 30 years old, female, single and Catholic, and 73.33% of the students had already experienced some death experience with significant people in the family. The Neutral Acceptance dimension was the most prevalent, with an average of 5.4407, followed by the Approval Acceptance dimension with an average of 4.417, nursing technicians declared they were less afraid of death, students who had already experienced death with a significant person had more Escape Acceptance regarding death. It is important to provide spaces for discussions throughout academic teaching in order to strengthen convictions, raise awareness of behaviors favorable to humanized care centered on the patient and family.